ANALISIS PENGARUH KUALITAS AUDIT, KINERJA DANKECERDASAN EMOSIONAL AUDITOR TERHADAP PENGAMBILAN KEPUTUSAN - Yusnaldi, Yusnaldi; Pujiati, Herni; Anggraeni, Noerlina (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2025)
Professional accountant services are needed as a guarantee that the financial statementscan be trusted as a basis for decision making by internal and external parties. Many factorsaffect audit reports to be quality, among others, audit quality, auditor'sperformance andemotional intelligence. Therefore, the purpose of this study is to examine the effect of auditquality, performance and emotional intelligence on decision making. This research is aquantitative research with a descriptive approach. Sampleselection using simple randomsampling method. The population in this study is the auditor who works at the PublicAccountant Office in the Jakarta Region which consists of 9 KAPs who are willing to fill inthe questionnaire there are 5 KAPs. From the questionnaire distributed there were 42respondents who were in accordance with the criteria for determining the sample. The datais collected and analyzed using descriptive statistics, instinct test, class assumption test,multiple regression analysis and hypothesis presentation.The elaboration results above can be concluded that partially audit quality variables, andemotional intelligence have a significant effect on decision making, but performance doesnot significantly influence decision making. Simultaneously audit quality,performance andemotional intelligence have a significant effect on decision making at the Public AccountingFirm in the Jakarta Region.